RESEÑA de : López Barja de Quiroga, P.; Lomas Salmonte, F.J. Historia de Roma. Madrid : Ediciones Akal, S.A., 2004 - Javier Cabrero Piquero (Espacio, Tiempo y Forma. Serie II, Historia Antigua, 2005)
-